Interictal Single-Voxel Proton Magnetic Resonance Spectroscopy of the Temporal Lobe in Dogs With Idiopathic Epilepsy - Olszewska, Agnieszka; Schmidt, Martin Jürgen; Failing, Klaus; Nicpoń, Józef; Podgórski, Przemysław; Wrzosek, Marcin Adam (Frontiers in Veterinary Science, 2020)
Abstract Proton magnetic resonance spectroscopy (H1-MRS) could provide insight into the metabolic pathophysiology of the temporal lobe of canine brain after seizure. Currently, there is no evidence-based data available on magnetic resonance spectroscopy (MRS) of temporal lobe in dogs with idiopathic epilepsy. The aim of this prospective, cross-sectional study was, to evaluate the interictal metabolic activity of the temporal lobe in idiopathic epilepsy dogs compared to a control group with the use of H1-MRS. Ten healthy dogs and twenty-seven client-owned dogs with idiopathic epilepsy underwent 1.5 Tesla magnetic resonance imaging (MRI) and single-voxel H1-MRS. The MRS studies were acquired as spin echoes with a repetition time (TR) of 2,000 milliseconds, an echo time (TE) of 144 milliseconds. A cubic voxel (10 x 10 x 10 mm) was positioned bilaterally, into the region of left and right temporal lobe, including a middle part of the hippocampus and the amygdala. The NAA-to-creatine (NAA/Cr), NAA-to-choline (NAA/Cho), choline-to-creatine (Cho/Cr), and choline-to-NAA (Cho/NAA) ratios were determined in both hemispheres and compared to controls. No significant differences in all metabolite ratios between epileptic dogs and the control group could be found. A time-dependent decrease in the NAA/Cho ratio as well as an increase in the Cho/NAA ratio was found with proximity in time to the last seizure. We found no correlation between metabolite ratios and age or sex in this animal group. Timespan from the last seizure to the acquisition of MRS significantly correlated with NAA/Cho and Cho/NAA ratio. We conclude that without a time relation, metabolite ratios in dogs with idiopathic epilepsy do not differ from the control group.